Transfer of a Self-Expanding Stent to a Braided Microcatheter with the Aid of Transcatheter Illumination: Technical Report and Illustrative Case - Broadbent, L. Paul (AJNR Am J Neuroradiol, 2003)
Summary: A new self-expanding stent approved for the treatment of wide-necked intracranial aneurysms can be difficult to deploy in tortuous vascular anatomy. Some of the difficulty may be attributed to deformation of the delivery microcatheter. We describe a technique for transferring the stent into a braided microcatheter.